Critical Review : Integrating Target Language Culture into Teaching Foreign Languages - Nguyen Thi Dao, (International Journal of Scientific Research in Science and Technology, 2024)
A language is used to express its culture. A culture is incorporated into a language. So, when teaching a language, it is necessary to integrate the culture into teaching the language of that culture. For this reason, this paper reviews the relationship between language and culture and offers several recommendations for incorporating target language culture into foreign language teaching, including: exposing Students to Authentic Materials, contrasting the target language's culture with that of the students, presenting live native speakers to your pupils.
Keywords: Target Language Culture; Teaching Foreign Languages; Integrating Culture Into Teaching Languages